Human myiasis in Ecuador. - Manuel Calvopina; Esteban Ortiz-Prado; Byron Castañeda; Isabel Cueva; Richar Rodriguez-Hidalgo; Philip J Cooper (Public Library of Science (PLoS), 2020)
We review epidemiological and clinical data on human myiasis from Ecuador, based on data from the Ministry of Public Health (MPH) and a review of the available literature for clinical cases. The larvae of four flies, Dermatobia hominis, Cochliomyia hominivorax, Sarcophaga haemorrhoidalis, and Lucilia eximia, were identified as the causative agents in 39 reported clinical cases. The obligate D. hominis, causing furuncular lesions, caused 17 (43.5%) cases distributed along the tropical Pacific coast and the Amazon regions. The facultative C. hominivorax was identified in 15 (38%) clinical cases, infesting wound and cavitary lesions including orbital, nasal, aural and vaginal, and occurred in both subtropical and Andean regions. C. hominivorax was also identified in a nosocomial hospital-acquired wound. Single infestations were reported for S. haemorrhoidalis and L. eximia. Of the 39 clinical cases, 8 (21%) occurred in tourists. Ivermectin, when it became available, was used to treat furuncular, wound, and cavitary lesions successfully. MPH data for 2013-2015 registered 2,187 cases of which 54% were reported in men; 46% occurred in the tropical Pacific coast, 30% in the temperate Andes, 24% in the tropical Amazon, and 0.2% in the Galapagos Islands. The highest annual incidence was reported in the Amazon (23 cases/100,000 population), followed by Coast (5.1/100,000) and Andes (4.7/100,000). Human myiasis is a neglected and understudied ectoparasitic infestation, being endemic in both temperate and tropical regions of Ecuador. Improved education and awareness among populations living in, visitors to, and health personnel working in high-risk regions, is required for improved epidemiological surveillance, prevention, and correct diagnosis and treatment.